Design, Development and Testing of Shape Shifting Wing Model - Dean Ninian; Sam M. Dakka (Aerospace, 2017)
The design and development of morphing (shape shifting) aircraft wings—an innovative technology that has the potential to increase the aerodynamic efficiency and reduce noise signatures of aircrafts—was carried out. This research was focused on reducing lift-induced drag at the flaps of the aerofoil and to improve the design to achieve the optimum aerodynamic efficiency. Simulation revealed a 10.8% coefficient of lift increase for the initial morphing wing and 15.4% for the optimized morphing wing as compared to conventional wing design. At angles of attack of 0, 5, 10 and 15 degrees, the optimized wing has an increase in lift-to-drag ratio of 18.3%, 10.5%, 10.6% and 4% respectively when compared with the conventional wing. Simulations also showed that there is a significant improvement on pressure distribution over the lower surface of the morphing wing aerofoil. The increase in flow smoothness and reduction in vortex size reduced pressure drag along the trailing edge of the wing as a result an increase in pressure on the lower surface was experienced. A morphing wing reduced the size of the vortices and therefore the noise levels measured were reduced by up to 50%.